Profil Tekanan Darah, Kontraksi Rahim, dan Denyut Jantung Janin pada Gravida dengan Terapi Neuroprotektan di RSUD Dr. Saiful Anwar : Profile of Blood Pressure, FHR, and Uterine Contractions Of Gravid Women with MgSO4 Neuroprotectant Therapy at HCU Ranu Grati RSUD Dr. Saiful Anwar - Sagita, Rahma Furi; Purwaningsih, Tri; Azizah, Firda; Damayanty, Ayu; Amila, Ruri (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Background: Neuroprotectants are substances used to protect the nerves of fetuses at risk of premature birth. Administration of MgSO4 as a neuroprotectant is one of the interventions given to gravida at risk of premature birth at Dr. Saiful Anwar Hospital. MgSO4 has a vasodilator side effect that is thought to cause a hypotensive effect. Magnesium also has a relaxing effect on smooth muscles which is expected to have the effect of reducing uterine contractions. It is not yet known how MgSO4 affects fetal heart rate. Aim: This study aims to determine the condition of maternal blood pressure, maternal uterine contractions, and fetal heart rate when MgSO4 is administered at the Ranu Grati HCU, Dr. Saiful Anwar Hospital in 2022-2023. Method: Retrospective descriptive study using secondary data. Data were collected from medical records from January 2022 to December 2023 at the Ranu Grati HCU, Dr. Saiful Anwar Hospital. The subjects in this study were all clinical data of gravida patients who received MgSO4 therapy as a neuroprotectant. Preeclampsia gravida patients who received MgSO4 were included in the exclusion criteria. Results: The study or 36 respondents, showed the average of systolic blood pressure of respondents decreasing up to 6,469 mmHg at 16thof MgSO4 admisnistration, then at the 24th hour of administration, systolic blood pressure increased by 0.3 mmHg. The average of diastolic blood pressure decreased by 4.4723 mmHg which occurred from the 0th hour to the 24th hour. Fetal Heart Rate showed a decrease in DJJ frequency of an average of 5,2x/minute. In uterine contractions, 91.7% of patients did not experience uterine contractions during neuroprotectant administration. Conclusion: Neuroprotectant administration has an insignificant effect on reducing blood pressure, fetal heart rate, and maternal uterine contractions. Keywords: Neuroprotectant; MgSO4